Comparative Study of Ultrasound Guided FNAC and Conventional FNAC in the Diagnosis of Parotid Tumour (Bangladesh Journal of Otorhinolaryngology, 2015)
Objective: To evaluate role of ultrasound guided FNAC for the diagnosis of parotid tumor.Methods: This cross sectional study was conducted in 39 patients with parotid tumor admitted in the ENT department of out door of Bangabandhu Sheikh Mujib Medical University, Dhaka Medical College Hospital, and Sir Salimullah Medical College and Mitford Hospital Dhaka, during July 2013 to June 2014 were enrolled for surgical management. Conventional FNAC and ultrasound guided FNAC were done in all these patients and they were followed up from the admission upto the post operative tissue diagnosis of parotid tumor in respective pathology departments for histopathological correlation.Results: The highest incidence of parotid tumor was in 4th decade and male to female ratio was almost 1:1. The main clinical feature were 27(69.2%) had firm, 6(15.4%) soft, 1(2.6%) hard and 5(12.8%) over the parotid tail. The validity of histopathology evaluation for pleomorphic in USG FNAC sensitivity 95.7%, specificity 100.0%, accuracy 97.4%, positive predictive values 100.0%, negative predictive values 94.1%. Evaluation for Meucoepidermoid sensitivity 80.0%, specificity 97.1%, accuracy 94.9%, positive predictive values 80.0%, negative predictive values 97.1% in USG FNAC. In USG FNAC for identification Warthin sensitivity 100.0%, specificity 100.0%, accuracy 100.0%, positive predictive values 100.0%, negative predictive values 100.0%. Evaluation for Adenocystic in USG FNAC sensitivity 100.0%, specificity 100.0%, accuracy 100.0%, positive predictive values 100.0%, negative predictive values 100.0%.Conclusion: It can be concluded that Ultrasound guided FNAC has definite value in the diagnosis of tumours and can be regarded as a sensitive and specific imaging modality for pre-operative discrimination of the benign and malignant parotid tumours.Bangladesh J Otorhinolaryngol; April 2015; 21(1): 5-16